The Synthesis of 2D CH3NH3PbI3 Perovskite Films with Tunable Bandgaps by Solution Deposition Route - Vorrada Loryuenyong; Pajaree Thongpon; Sasathorn Saudmalai; Achanai Buasri (International Journal of Photoenergy)
Nowadays, organo-lead halide is one of the most interesting materials for perovskite solar cells. This is because of its ease of fabrication, long absorption wavelength region, and long diffusion length. In this study, we investigated the bandgap tuning of hybrid mixed-halide perovskite films. The films were prepared by sequential two-step deposition technique, using 5-ammonium valeric acid iodide (5-AVAI), PbI2, and a mixture of CH3NH3I and CH3NH3Br as precursor solutions. The results confirmed the formation of 2D perovskites in the presence of 5-AVAI. The obtained films had higher moisture resistance, better surface coverage, and smaller grain size, compared to the films without 5-AVAI. With the introduction of Br− ions, the change in the lattice parameter was observed. The bandgap was also found to increase with increasing Br− content.